Development of robotic polishing/fettling system on ceramic pots. (6th May 2021) - Yu, Zhangguo; Lin, Hsien-I
Current robot polishing techniques are available for objects with computer-aided design geometric models but not for objects without geometric models such as ceramic or clay pots. In this study, we developed a robotic polishing/fettling system to polish the molding defects of ceramic objects. The polishing force on the object surfaces is required to be constant to obtain better results. Thus, the proposed robotic polishing system was designed with a stepper motor, ball screw, and force sensor. The proposed system acquired a rough robot polishing/fettling trajectory and adopted a fuzzy proportional–integral–derivative controller to regulate the trajectory to maintain the desired contact force response from a ceramic object. We developed the temporary desired value technique to make the polishing force response close to the desired one. We validated the system on a six-degrees-of-freedom Staubli TX 40L robotic arm. Experiments were performed to test the effectiveness of the system. The robot trajectory responses showed that the proposed system performed well in tracking the desired force in the polishing/fettling process. We used a 3D microscope to verify that the molding defect of the ceramic pot was significantly removed to evaluate the polishing/fettling quality.